Analysis of Negative Behaviour in Nursing Workplace and The Impact - M.Noer, Rachmawaty; Arif, Yulastri; Wardhani, Utari Ch. (Universitas Islam Lamongan, 2020)
The hospital is one of the health service institutions involved in various activities so it is easy to happen. One of the Nurses' health workers is the most health resource in the hospital that receives a negative relationship. Negative behavior faced by nurses can cause problems for the hospital. The purpose of this study was to analyze the negative behavior received by nurses in Batam city hospitals. This type of research is quantitative research with cross-sectional design. The number of samples in this study were 359 nurses distributed in several hospitals in the city of Batam. The results showed several types of negative interactions received by nurses in the workplace (71.3%) and intimidation (28.7%). The results showed there was a relationship that illustrates the work stress with the negative received by nurses (p value <α = 0.05). How can the hospital make policies related to this policy? What to do?